Machines that work by electric current - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
We are surrounded by machines that work by electric current. For example, digital devices that work by electric current like clock or transducer. In order for them to work, they require current. This paper explains a simple way to make those devices.